Acceptance and Perceptions of COVID-19 Booster Dose; A Survey among Residents of Rawalpindi - Rashid, Zubaida; Mashhadi, Syed Fawad; Rashid, Maryam; Viqar, Sarah; Tabassam, Marya; Tariq, Amna (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To determine public acceptance of COVID-19 booster dose, to know about perceptions and possible barriers regarding the vaccine.Study design: Analytical cross sectional study.Place and Duration of Study: conducted regarding the acceptance and perception of the vaccine booster dose among the residents of Rawalpindi Pakistan. The duration of study was 3 months i.e. from Jun till Aug 2022Methodology: The sample size was 320 and collected using convenient sampling technique. The study included residents of Rawalpindi between ages 18 and 65. Google forms based on Health Belief Model were used for data collection. Data analysis was done using SPSS version 28 and summary statistics were produced using frequencies, percentages and mean. Chi-square test was also used to determine associations between categorical variables.Results: The results revealed that 74% of the participants’ primary reason for getting booster dose was their own safety while major barrier to booster dose vaccination was side effects related to vaccine - 62%. 81.3% people were willing to get the booster dose and 87.9% people agreed to receive booster dose for free. Chi-square test indicated a significant association between acceptance and perceived susceptibility, benefits and severity.Conclusion: In conclusion, our findings reveal that majority of people were willing to get booster dose primarily for own safety. However, counselling is required to decrease the perceived barriers to vaccination regarding side effects of the vaccine.